105k views
2 votes
Two problems here I need solved! I need every step, so please have that with your answers!!

1. Solve this rational equation:


(1)/((x-4))+(x)/((x-2))=(2)/(x^(2)-6x+8)


1. Solve this radical equation:


√(x+11) -x=-1

User Franta
by
5.3k points

1 Answer

7 votes
QUESTION 1

We want to solve,


(1)/((x-4))+(x)/((x-2))=(2)/(x^(2)-6x+8)

We factor the denominator of the fraction on the right hand side to get,


(1)/((x-4))+(x)/((x-2))=(2)/(x^(2)-4x - 2x+8).

This implies

(1)/((x-4))+(x)/((x-2))=(2)/(x(x-4) - 2(x - 4)).


(1)/((x-4))+(x)/((x-2))=(2)/((x-4)(x - 2))

We multiply through by LCM of

(x-4)(x - 2)


(x - 2) + x(x-4) = 2

We expand to get,


x - 2 + {x}^(2) - 4x= 2

We group like terms and equate everything to zero,


{x}^(2) + x - 4x - 2 - 2 = 0

We split the middle term,


{x}^(2) + - 3x - 4 = 0

We factor to get,


{x}^(2) + x - 4x- 4 = 0


x(x + 1) - 4(x + 1) = 0


(x + 1)(x - 4) = 0


x + 1 = 0 \: or \: x - 4 = 0


x = - 1 \: or \: x = 4

But

x = 4
is not in the domain of the given equation.

It is an extraneous solution.


\therefore \: x = - 1
is the only solution.

QUESTION 2


√(x+11) -x=-1

We add x to both sides,


√(x+11) =x-1

We square both sides,


x + 11 = (x - 1)^(2)

We expand to get,


x + 11 = {x}^(2) - 2x + 1

This implies,


{x}^(2) - 3x - 10 = 0

We solve this quadratic equation by factorization,


{x}^(2) - 5x + 2x - 10 = 0


x(x - 5) + 2(x - 5) = 0


(x + 2)(x - 5) = 0


x + 2 = 0 \: or \: x - 5 = 0


x = - 2 \: or \: x = 5

But

x = - 2
is an extraneous solution


\therefore \: x = 5
User Hachi
by
5.8k points